Spatial Model of Geographic Distribution of Leprosy Cases in East Java Province, Indonesia - Makful, Martya Rahmaniati; Handayani, Yolanda; Nugraha, Fajar (Universitas Negeri Semarang (UNNES) in cooperation with the Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2024)
Leprosy is an infectious disease and serious health problem that causes disability. According to the World Report on Disability from the World Health Organization (WHO), leprosy is one of the main causes of disability. It can be transmitted through inhalation or contact with patients, which allows it to spread easily and generally occurs in developing countries, including Indonesia. The number of leprosy cases in Indonesia also fluctuates every year, particularly in East Java Province. This study aimed to apply leprosy spatial modeling by evaluating the heterogeneity of data distribution in East Java Province. Using data from the health profile of the East Java Province, the study analyzed socioeconomic variables, access to health services, and the condition of the home environment. Spatial analysis using Moran’s Index and the Spatial Error Model was employed to obtain spatial distribution and modeling patterns. Variables such as Human Development Index, poverty, access to healthcenters, and the physical condition of the home environment spatially affect leprosy cases. Cross-sectoral collaboration is needed to address leprosy cases.